The Effect of Customer Experience and Customer Identification On Customer Engagement Through Behavioral Intention As A Moderation Variable (Customers of the General Dental and Oral Polyclinic of Bunda Hospital Padang) - Ika Christianti, Indira; Kasni Astiena, Adila; Febrian (Jurnal Manajemen dan Keuangan, 2025)
This study aims to prove the influence of customer viralslot experience, customer identification and behavioral intention on customer engagement, in addition this study also aims to prove the role of behavioral intention in moderating the relationship between customer experience and customer identification with customer engagement viralslot. This study was conducted on patients of the general dental and oral polyclinic of Bunda Padang Hospital. The sample size used was 120 people selected using the purposive sampling method. The data collection technique was carried out by survey, while the data analysis technique used was Moderating Regression Analysis (MRA). In accordance with the results of the first hypothesis test, it was found that customer experience had a positive effect on customer engagement at the general dental and oral polyclinic of Bunda Padang Hospital, but at the second hypothesis test stage, customer identification did not have a significant effect on customer engagement, but at the third hypothesis stage, it was successfully proven that behavioral intention had a positive and significant effect on customer engagement at the general dental and oral polyclinic of Bunda Padang Hospital. In the third hypothesis testing stage, it was found that behavioral intention was able to strengthen the relationship between customer experience and customer engagement at the general dental and oral polyclinic of Bunda Padang Hospital, but failed to prove that customer experience was able to moderate the relationship between customer identification and customer engagement at the general dental and oral polyclinic of Bunda Padang Hospital viralslot